The Relationship between Return and the Bid-Ask Spread in Tehran Stock Exchange - Hasan Ghalibaf Asl (تحقیقات مالی, 2012)
This paper studies the relationship between return and the Bid-Ask Spread in Tehran Stock Exchange. The research has been done according to Amihud and Mendelson’s model (1986). It should be mentioned that portfolio beta and size are added as explanatory variables into the model. The study period is from Day 1382 to Tir 1389. Based on the pooling of cross section and time series data used to estimate and test the model, the obtained results confirmed that there is a positive relationship between the market-observed return and the Bid-Ask Spread in Tehran stock exchange same as Amihud and Mendelson’s model.